## Monday, February 6, 2012

### Converting a number from base 10 to base 6

steps to convert to base 6 from base 10

Ill illustrate by example and explain each step as I go.

First you will set up your problem.  lets say we want to convert 200 to base 6

the problem will be set up as follows  200 =      x  6  +        in the first  blank,     , we divide 200 by 6 and drop the remainder which is 33  which makes our problem look like this 200 = 33 x 6 +
now for the second blank we place the remainder,  which we dropped in the first step  which gives us this:
200 = 33 x 6 + 2

The next step is you take the 33 and repeat what you did in the first step and placing it under the first part of or problem   like this

200 = 33 x 6 + 2
33   =  5  x 6 +3

Then you take the 5 and do the same thing. and you end up with  200 = 33 x 6 + 2
33   =  5  x 6 +3
5  =   0 x 6  + 5
You then will take the remainders and from bottom to top and you get 532

This method works when converting to other bases as well